Implementasi dan Evaluasi Manajemen Pendidikan Islam di MAN 2 Padangsidimpuan - Nur Apnilelawati; Fahrul Sanawi; Syafaruddin Syafaruddin; Makmur Syukri (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The purpose of this study was to determine the extent to which the implementation and evaluation of Islamic education management in MAN 2 Model Padangsidimpuan. To find out the success of the education program implemented, an evaluation is needed, which is called program evaluation. This research uses descriptive research method. This research method is a method that seeks to reveal the facts of an event, object, activity, process, and human as it is at the present time or a period that is still possible in the respondent's memory. The results of the study include there are macro and micro policies in Islamic education management at MAN 2 Padangsidimpuan. Macro policies for teachers to develop educational policies that have been set by the government, especially those related to the curriculum. In compiling an annual, semi-annual, quarterly, or lesson unit program, it must have the same components, namely objectives, lesson materials, learning methods and media, and evaluation, only the breadth and depth are different. The principal's policy towards increasing teacher professional competence at MAN 2 Padangsidimpuan from a macro perspective is that teachers are required to make learning tools: annual programs, semester programs, syllabus, and complete lesson plans in accordance with the 2013 curriculum. Micro policy, a policy made by the head of the madrasa, namely by increasing teacher competencies, including the professional competence of teacher professionalism. The policies are conducting professional coaching which includes: (1) seminar; (2) discussion; (3) training; (4) technical guidance/guidance by tutors/tutorials in class and teacher working groups (KKG).